Identification of influenza A nucleoprotein body domain residues essential for viral RNA expression expose antiviral target. Issue 1 (December 2017) - Davis, Alicia; Ramirez, Jose; Newcomb, Laura
Abstract Background Influenza A virus is controlled with yearly vaccination while emerging global pandemics are kept at bay with antiviral medications. Unfortunately, influenza A viruses have emerged resistance to approved influenza antivirals. Accordingly, there is an urgent need for novel antivirals to combat emerging influenza A viruses resistant to current treatments. Conserved viral proteins are ideal targets because conserved protein domains are present in most, if not all, influenza subtypes, and are presumed less prone to evolve viable resistant versions. The threat of an antiviral resistant influenza pandemic justifies our study to identify and characterize antiviral targets within influenza proteins that are highly conserved. Influenza A nucleoprotein (NP) is highly conserved and plays essential roles throughout the viral lifecycle, including viral RNA synthesis. Methods Using NP crystal structure, we targeted accessible amino acids for substitution. To characterize the NP proteins, reconstituted viral ribonucleoproteins (vRNPs) were expressed in 293 T cells, RNA was isolated, and reverse transcription – quantitative PCR (RT-qPCR) was employed to assess viral RNA expressed from reconstituted vRNPs. Location was confirmed using cellular fractionation and western blot, along with observation of NP-GFP fusion proteins. Nucleic acid binding, oligomerization, and vRNP formation, were each assessed with native gel electrophoresis. Results Here we report characterization of an accessible and conserved five amino acid region within the NP body domain that plays a redundant but essential role in viral RNA synthesis. Our data demonstrate substitutions in this domain did not alter NP localization, oligomerization, or ability to bind nucleic acids, yet resulted in a defect in viral RNA expression. To define this region further, single and double amino acid substitutions were constructed and investigated. All NP single substitutions were functional, suggesting redundancy, yet different combinations of two amino acid substitutions resulted in a significant defect in RNA expression, confirming these accessible amino acids in the NP body domain play an important role in viral RNA synthesis. Conclusions The identified conserved and accessible NP body domain represents a viable antiviral target to counter influenza replication and this research will contribute to the well-informed design of novel therapies to combat emerging influenza viruses.